What drives foreign direct investment: the role of language, geographical distance, information flows and technological similarity - Ly, A.; Esperança, J.; Davcik, N. S. (Journal of Business Research, 2018)
This paper sheds new light on the impact of linguistic and technological similarities between countries on foreign direct investment (FDI), using an extended gravity model. The model includes technological commonality, as measured by the aggregate production of intellectual property, at the country level. An analysis of 71,309 pairs of FDI relationships, from 2000 to 2012, showed that language is positively associated with a high level of FDI. Technological differences do impede the flow of FDI between countries, and information flow is crucial for large flows of FDI. Information flow diminishes the negative impact of distance.